The Importance of Impact Loading and the Stretch Shortening Cycle for Spaceflight Countermeasures - Gruber, Markus; Kramer, Andreas; Mulder, Edwin; Rittweger, Jörn (Frontiers in Physiology, 2019)
Pronounced muscle and bone losses indicate that the musculoskeletal system suffers substantially from prolonged microgravity. A likely reason for these detrimental adaptations in the lower extremity is the lack of impact loading and the difficulty to apply large loading forces on the human body in microgravity. The human body is well adapted to ambulating in earth’s gravitational field. A key principle herein is the periodic conversion of kinetic to elastic energy and vice versa. Predominantly tendons and to a lesser extent muscles, bones and other tissues contribute to this storage and release of energy, which is most efficient when organized in the stretch-shortening-cycle (SSC). During SSC, muscles, especially those encompassing the ankle, knee and hip joints, are activated in a specific manner, enabling the production of high muscle forces and elastic energy storage. In consequence, the high forces acting throughout the body deform the viscoelastic biological structures sensed by mechanoreceptors and feedback in order to regulate the resilience of these structures and keep strains and strain rates in an uncritical range. Recent results from our lab indicate, notably, that SSC can engender a magnitude of tissue strains that cannot be achieved by other types of exercise. The present review provides an overview of the physiology and mechanics of the natural SSC as well as the possibility to mimic it by the application of whole body vibration. We then report the evidence from bed rest studies on effectiveness and efficiency of plyometric and resistive vibration exercise as a countermeasure. Finally, implications and applications of both training modalities for human spaceflight operations and terrestrial spin-offs are discussed.